Technical investigations of iron-working remains from the French Jesuit mission of Sainte-Marie among the Hurons (1639-1649) - Sandra K. Zacharias; James R. Hunter; Ursula M. Franklin (Canadian Institute of Mining, Metallurgy and Petroleum, 1999)
Archaeometallurgical remains can be a valuable source of information about past technological activities and, by inference, the societies that undertook them. Material traces of former metal-producing or metal-working centres can include raw materials, products, or metallurgical installations such as mines, furnaces or forges. Of these remains, the most common is slag, often left undisturbed since its original production. Physical and chemical analyses of archaeological slag and metal can often reveal the processes and materials involved in their formation. Mineral composition and softening temperature of a slag, for instance, can indicate the conditions of the metallurgical operation, such as temperature and atmosphere and, thus, help identify metallurgical processes which took place at a site(1). The present report illustrates the value of such analysis. Metal-working remains from Sainte-Marie among the Hurons, near Midland, Ontario, on the south side of Georgian Bay have been analyzed in order to determine the techniques and processes used by the 17th-century blacksmith who worked at the mission headquarters from 1642 to 1649. Samples were selected from a very large collection of blacksmith refuse which was excavated from the site by archaeologist Kenneth Kidd in 1941-42(2).